2019
DOI: 10.1016/j.rboe.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Técnica de Stoppa modificada para fratura de acetábulo: uma revisão

Abstract: ResumoFraturas acetabulares são lesões graves e desafiadoras para cirurgiões ortopédicos. As abordagens anterior e posterior foram descritas para a fixação dessas fraturas. A técnica de Stoppa modificada é considerada uma alternativa à abordagem anterior, que fornece acesso à pelve pelo interior da cavidade. O objetivo do presente artigo é revisar a literatura disponível sobre o uso da abordagem de Stoppa modificada em fraturas de acetábulo. Os dados disponíveis sugerem que a abordagem de Stoppa modificada é ú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(282 reference statements)
0
8
0
Order By: Relevance
“…Likewise in this examination, Kazemi et al [18] announced that the mean changed Merle d'Aubigne Score was 17.4, interestingly Elmadag et al [35] detailed that I in 40.9% and Poor in 13.9% of the patients. Whereas Matta's radiological score in last visit of follow-up was Excellent in 63%, Good in 20%, Fair in 8.5% and Poor in 8.5% of the patients, in contrast Soni et al [36] reported that in ORIF group, Matta's radiological score in last visit was Excellent in 64.3%, Good in 20%, Fair in 8.6% and Poor in 7.1% of the patients also Cole et al (37) reported that in ORIF group, Matta's radiological score in last visit was Excellent in 64%, Good in 25%, Fair in 7% and Poor in 4% of the patients.…”
Section: Utilitarian Resultsmentioning
confidence: 76%
“…Likewise in this examination, Kazemi et al [18] announced that the mean changed Merle d'Aubigne Score was 17.4, interestingly Elmadag et al [35] detailed that I in 40.9% and Poor in 13.9% of the patients. Whereas Matta's radiological score in last visit of follow-up was Excellent in 63%, Good in 20%, Fair in 8.5% and Poor in 8.5% of the patients, in contrast Soni et al [36] reported that in ORIF group, Matta's radiological score in last visit was Excellent in 64.3%, Good in 20%, Fair in 8.6% and Poor in 7.1% of the patients also Cole et al (37) reported that in ORIF group, Matta's radiological score in last visit was Excellent in 64%, Good in 25%, Fair in 7% and Poor in 4% of the patients.…”
Section: Utilitarian Resultsmentioning
confidence: 76%
“…Of the 11 patients included in the study (11 out of 26 patients with acetabulum anterior wall fracture), nine were male (81.82%), and two were female (18.18%). The median age of the patients at the time of trauma was 40 , and the median time to surgery was six days (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), and the median operation time was 120 minutes (90-180). The median amount of intraoperative bleeding was 450 ml (200-800) according to the measurement described by the study of Açan et al [14] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are publications stating that the modified Stoppa approach has a better anatomical reduction chance and lower complication rates compared to the ilioinguinal approach [10][11][12]. In addition, acetabulum anterior wall fractures have also been reported as complications of total hip replacement surgery, and anterior wall fractures treated with a modified Stoppa approach simultaneously with total hip replacement surgery are also presented in the literature [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these approaches require the placement of an incision on the abdominal wall and the intraoperative exposure of the abdominal soft tissue 7 . If the pelvic organs or other soft tissues are accidentally damaged during the surgical procedure, this can lead to incisional hernia, post-Pfannenstiel pain syndrome, rectus atrophy, urinary bladder injury, and other complications [8][9][10][11][12] . For some patients concerned about esthetic outcomes, the scar on the abdominal wall after the surgical procedure is also unacceptable.…”
mentioning
confidence: 99%